Modeling of tunable structures for optical digital mirror applications - Zhang, Wu (2009)
Optical filter is the device to isolate the transmitted light with certain wavelength so that the selecting particular information from a big amount becomes possible. The tunable optical filter, which can select different wavelength light under different condition, further improves the wavelength isolation function. However, the tuning speed of the optical filters currently used is not fast enough; in addition, the power consuming of such filters is not low, which is not desirable. In this project, Fabry-Perot resonator based tunable optical filter using MEMS technology are designed and simulated to achieve a single/double mode(s) output within a certain spectrum range. Then different tuning methods were applied to test the tuning effect on the output. In the end, Bragg mirror based resonator is studied to achieve a tunable dual wavelength output which can be widely used in THz wave generator, communication and detection field. During this project, the output of the filter and resonator is simulated, during which the structure of the filter and resonator, such as the thickness of the silicon slab, the width of the air gap and the width of the cavity are modified to test the effect to the output of the device. In addition, the thermal tuning is also studied on the corresponding device, which can directly tune the refractive index of silicon, and in turn achieve the tune effect on the output. After the simulation, the simulation result was analyzed to get conclusion how the output will be tuned under different tuning scheme. By using this conclusion, a resonator is carefully designed which will give single mode output each from the two mirrors. This enables us to get the tunable dual wavelength output.